Faith in empire : religion, politics, and colonial rule in French Senegal, 1880-1940 - Foster, Elizabeth Ann, 1976- (Stanford, California : Stanford University Press, 2013)
'Faith in Empire' is an innovative exploration of French colonial rule in West Africa, conducted through the prism of religion and religious policy. It examines the relationships among French Catholic missionaries, colonial administrators, and Muslim, animist, and Christian Africans in colonial Senegal between 1880 and 1940. In doing so, it illuminates the nature of the relationship between the French Third Republic and its colonies, reveals competing French visions of how to approach Africans, and demonstrates how disparate groups of French and African actors, many of whom were unconnected with the colonial state, shaped French colonial rule.
To mock a nun : religion and politics in Senegal's communes, 1882-1890 -- Rivalry in translation : Catholicism, Islam, and French rule of the North-West Sereer, 1890-1900 -- "The storm approaches" : laicite and West Africa, 1901-1910 -- Proving patriotism : Catholic missionaries and the First World War in Senegal -- An ambiguous monument : Dakar's colonial cathedral of the Souvenir Africain -- Civilization, custom, and controversy : Catholic conversion and French rule in Senegal -- Conclusion : the limits of civilizing, 1936-1940.
Print version record.
Includes bibliographical references and index.
Master record variable field(s) change: 650
Keywords: Catholic Church -- Senegal -- History -- 19th century; Catholic Church -- Senegal -- History -- 20th century; Catholic Church; Religion and state -- Senegal -- History -- 19th century; Religion and state -- Senegal -- History -- 20th century; Religion and politics -- Senegal -- History -- 19th century; Religion and politics -- Senegal -- History -- 20th century; Church and state -- Colonies -- France; France -- Colonies -- Africa -- Religion; France -- Politics and government -- 1870-1940.; POLITICAL SCIENCE -- Political Process -- Political Advocacy; French colonies; Politics and government; Religion; Religion and politics; Religion and state; Africa; France; Senegal; 1800-1999; Electronic books; History